1994
DOI: 10.1016/0165-2478(94)00158-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide: Cytokine-regulation of nitric oxide in host resistance to intracellular pathogens

Abstract: To discover how nitric oxide (NO) synthesis is controlled in different tissues as cells within these tissues combat intracellular pathogens, we examined three distinctively different experimental murine models designed for studying parasite-host interactions: macrophage killing of Leishmania major; nonspecific protection against tularemia (Francisella tularensis) by Mycobacterium bovis (BCG); and specific vaccine-induced protection against hepatic malaria with Plasmodium berghei. Each model parasite and host s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
1
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(147 citation statements)
references
References 37 publications
3
137
1
6
Order By: Relevance
“…Because we found that LPS and IFN-␥ led to a decrease in TfR mRNA levels and to an increase in ferritin synthesis, oxidative stress is unlikely to be involved in the above responses. Moreover, the H 2 O 2 activates IRP-1 without affecting IRP-2 (57), 2 whereas we observed that LPS/IFN-␥ treatment increased IRP-1 activity and dramatically decreased IRP-2 binding, changes that could be prevented by specific iNOS inhibitors (Fig. 2).…”
Section: Lps/ifn-␥-treated Raw 2647 Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…Because we found that LPS and IFN-␥ led to a decrease in TfR mRNA levels and to an increase in ferritin synthesis, oxidative stress is unlikely to be involved in the above responses. Moreover, the H 2 O 2 activates IRP-1 without affecting IRP-2 (57), 2 whereas we observed that LPS/IFN-␥ treatment increased IRP-1 activity and dramatically decreased IRP-2 binding, changes that could be prevented by specific iNOS inhibitors (Fig. 2).…”
Section: Lps/ifn-␥-treated Raw 2647 Cellsmentioning
confidence: 83%
“…It is now well established that cytostatic and cytotoxic effects of murine macrophages are caused in part by nitric oxide (NO) produced enzymatically by the stepwise oxidation of L-arginine to NO and L-citrulline (2,3). The cytotoxic function of NO requires that it is produced in relatively large quantities in macrophages and some other cells and this is accomplished by inducible NO synthase (iNOS) (3).…”
mentioning
confidence: 99%
“…The activation of the NF-κB-dependent iNOS promoter supports the inf lammation-mediated stimulation of iNOS transcription (30). Furthermore, iNOS produces large quantities of NO following stimulation by IL-1 and TNF-α (31).…”
Section: Discussionmentioning
confidence: 99%
“…effector molecules following their activation by IFN-γ and TNF [17,18]. Therefore, we assessed whether the susceptibility to L. major in PIP KO mice was primarily related to the impaired Th1-cell (IFN-γ) response or is multifactorial, that is, also related to defective macrophage function.…”
Section: Impaired No Production and Parasite Kill In Macrophages Frommentioning
confidence: 99%